Comparing the oral language abilities of children with autism spectrum disorder and specific language impairment using the Comprehensive Assessment of Spoken Language (CASL) - Kritzinger, Alta M. (Aletta Margaretha) (University of Pretoria, 2015)
Dissertation (MComm Path)--University of Pretoria, 2015.